Peningkatan Hasil Belajar Mata Kuliah Media Pembelajaran Matematika Melalui Flipped Clasroom Berbantuan Schoology - Dodik Mulyono; As Elly S; Atika Nur Hidayati (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Negeri Jakarta, 2020)
The purpose of this study was to improve learning outcomes of mathematics learning media through flipped classrooms aided by school logic lms. The results of the study on pre-cycle showed the student learning outcomes obtained were 3 students who completed or 11.54%, then after being given an action using flipped classrooms assisted by schoology, there was an increase in learning outcomes with students who completed in Cycle I by 34.61%, Cycle II at 61.54% and cycle III at 100%. From the results of the percentage experiencing success in the third cycle that meets the success indicator that is> 75% complete. Thus these results indicate that an increase in student learning outcomes by applying mathematics learning media through flipped classrooms assisted by schoology can improve learning outcomes of student mathematics learning media